THE RELATIONSHIP BETWEEN CREATIVE THINKING SKILLS AND STUDENTS' SCIENCE LITERACY ABILITY - Eka Maryam (Adisam Publisher, 2025)
This study analyses the relationship between creative thinking skills and students' science literacy skills. Creative thinking is essential in higher education, especially in Physics learning, which requires solving complex problems. Science literacy includes understanding, application, and the ability to communicate about scientific concepts. This study uses a quantitative method with a correlational approach. The results showed a significant relationship between creative thinking skills and students' science literacy, with a correlation coefficient of 0.85, which showed a positive relationship. These findings indicate that improving creative thinking skills can improve students' science literacy skills.